Χάρτης Βλάστησης "Περιοχή Κορυφές Όρους Βόρας GR1240001" Β. τμήμα - Α. Αποστολάκης; Π. Γκανατσάς; Γ. Γουδέλης; Ε. Ελευθεριάδου; Κ. Θεοδωρόπουλος; A. Apostolakis; P. Ganatsas; G. Goudelis; E. Eleutheriadou; K. Theodoropoulos (Ελληνικό Κέντρο Βιοτόπων-Υγροτόπων (ΕΚΒΥ), 1996)
LIFE